(untitled) (Journal of Governance and Development (JGD), 2023)
The digital economy in Yogyakarta, Indonesia assumed a pivotal part in keeping society working during the Coronavirus 2019 (COVID-19) pandemic by empowering remote working, mechanizing measures, and encouraging contactless exchanges. The expanded utilization of digital technologies likewise carried society closer to building up a digital economy. The digital platforms used during COVID-19 can drive recovery and solidify future services. This study analyzes how Yogyakarta’s Micro, Small, and Medium Enterprises (MSMEs) sector faced difficult situations for the economy during the pandemic and how the government implemented the digital economy for MSMEs to recover the economy. This qualitative study uses in-depth online interviews for primary data and supporting books, journals, documents, and regulations to characterize the background. The research findings of this study report on the implementation of a digital economy to improve the economic situation. Specifically, the Yogyakarta government targeted bolstering MSMEs, focusing on online platform application development. Second, MSME owners and customers alike benefit from the platforms. Online, MSME owners can quickly sell their goods and customers may choose and buy goods. Third, Information and Communications Technology (ICT) users for MSMEs increased compared to the previous year and encompassed 70 percent of the total MSMEs. The research contribution can help to solve the problems faced by government, business and society by decreasing economic risk.